Cross-Sectional Study on Mobile Phone Involvement Among Medical Students of a Tertiary Care Teaching Hospital of Western India - Mihir P Rupani; Khushali D Parikh; Atul V Trivedi; Manindra P Singh; Patel Ayushi; Vadodariya Bhakti; Bharat Bhagora; Bhawana Sharma (Medsci Publications, 2016)
Background: Mobile phones are said to be the new epidemic of this century. The research was carried out to assess the level of mobile phone involvement among the medical students and its determinants. Methodology: It was a cross-sectional study carried out among 150 medical students of Bhavnagar using a tool "Mobile Phone Involvement Questionnaire (MPIQ)". Results: Out of 150 medical students, 92.7% were highly involved with their mobile phone. Self reported data revealed that 40% often thought about their mobile phone when not using it; 50.4% often interrupt whatever else they are doing where they are contacted on their mobile phone; 78% often feel connected to others when they are using mobile phone; 39.3% often lose track of their mobile phone usage; 38.7% feel distressed by thought of being without their mobile phone and 35.9% often have been unable to reduce their mobile phone use. No association found between mobile phone involvement and age, gender, per-capita income, number of family members, expenditure on the phone or type of mobile plan. Conclusion: Most of the medical students (92.7%) were highly involved with their mobile phone, which was directly correlated with the frequency of their mobile phone usage.